Janus particles self-assembled from a small organic atypical asymmetric gemini surfactant. Issue 62 (19th July 2017) - Tang, Lei; Yang, Jun; Yin, Qinqin; Yang, Linghui; Gong, Deying; Qin, Feng; Liu, Junyang; Fan, Qin; Li, Jiahong; Zhao, Wenling; Zhang, Weiyi; Wang, Jiyu; et al.
Abstract : Gourd-shaped Janus particles could be self-assembled by single kind of small organic molecules. Abstract : A series of atypical asymmetric gemini surfactants with an amphiphilic carbonate group (–O–CO–O–) have been prepared. Some of these compounds could self-assemble in water into gourd-shaped Janus particles (JPs). Initial results suggested that the formation of JPs was highly likely to be related to their atypical gemini surfactant structure. To our knowledge, this is the first report on JPs that are self-assembled from a single kind of small organic molecule. We believe that our results will be utilized in many fields.